Genetically engineered Pseudomonas aeruginosa with lipase regulation for production of rhamnolipids from waste frying oil - Yang, Runyu; Shi, Yitong; Bian, Jinyu; Sun, Mengxiao; Ma, Junchi; Ren, Cailing; Feng, Xueyan; Wang, Yun; Yang, Yuanhui; Zhou, Jianqiang; Fu, Jun; Li, Ruijuan (Frontiers in Microbiology, 2025)
IntroductionRhamnolipids are valuable biosurfactants, but their large-scale application is limited by high production costs. Waste frying oil (WFO), a low-cost and abundant triglyceride-rich byproduct, offers a sustainable carbon source for rhamnolipid synthesis, though its utilization efficiency by microbes like Pseudomonas aeruginosa needs improvement.MethodsThis study evaluated the potential of engineered P. aeruginosa PAO1 strains (wild-type PAO1, aroA knockout PAO1ΔaroA, RhlAB/estA-overexpressing PAO1-RhlAB, lipase-overexpressing PAO1-lipase) for rhamnolipid production using WFO as the sole carbon source (soybean oil as positive control). Strategies to enhance WFO utilization—endogenous lipase overexpression and exogenous lipase addition (PAO1+, PAO1-lipase+ with repeated supplementation)—were also tested.ResultsWild-type PAO1 and PAO1ΔaroA could synthesize rhamnolipids from WFO, while PAO1-RhlAB improved yields vs. PAO1 in WFO. Exogenous lipase addition (PAO1+) achieved 14.0 g/L rhamnolipids at 48 h (vs. 9 g/L for PAO1), and the synergistic PAO1-lipase+ reached 16.0 g/L (vs. 12.8 g/L for PAO1-lipase) at the same time. At 144 h, PAO1-lipase+ had the highest oil degradation rate (34.40%), while PAO1+ maintained a slightly higher yield (20 g/L) than PAO1-lipase+ (19 g/L).DiscussionThese findings confirm that lipase regulation (overexpression or exogenous addition) enhances WFO utilization and rhamnolipid production, providing a cost-effective approach for sustainable rhamnolipid biosynthesis from waste lipids.